Physiological and Biochemical Responses of Commercial Strawberry Cultivars under Optimal and Drought Stress Conditions - Seyed Morteza Zahedi; Marjan Sadat Hosseini; Narjes Fahadi Hoveizeh; Saeid Kadkhodaei; Marek Vaculík (Plants, 2023)
Improving the extent of adaptation and the choice of the most tolerant cultivar is the first step to mitigating the adverse effects of limited water, especially in susceptible plants such as strawberries. To address this issue, two commercial strawberry cultivars (Camarosa and Gaviota) were compared when irrigated to match 100, 75, 50, and 25% field capacity (FC) to simulate the control, slight, moderate, and severe drought stress conditions, respectively. Drought stress induced the reduction of total chlorophyll, carotenoid, relative water content, and phenolic content significantly, whereas the activity of antioxidant enzymes, electrolyte leakage, osmolyte accumulation, and oxidative markers upsurged progressively in drought severity-dependent behavior. Gaviota produced more proline, hydrogen peroxide as a marker of membrane lipid peroxidation and disposed of by higher electrolyte leakage, significantly. On the other hand, Camarosa having higher soluble carbohydrates as well as enzymatic and non-enzymatic antioxidants could be considered a drought-tolerant cultivar. Genotypic variation between these cultivars could be used in breeding projects to promote drought-tolerant strawberries in the future.